Inconel 718 süperalaşımının termokimyasal borlanması - Dinç, Hasan (Fen Bilimleri Enstitüsü, 2013)
Borlama ısıl işlemi; difüzyon kontrollü bir yüzey sertleştirme prosesi olup, yüksek sıcaklıklarda bor atomlarının malzeme yüzeyine difüzyonu sonucu yüzeyde borür fazlarını içeren tabakaların meydana gelmesidir. Borlama ısıl işlemi demir esaslı ve demir dışı malzemelere uygulanabilmektedir. Ancak uygulama oranı olarak demir esaslı malzemeler (özellikle çelikler) ilk sırayı alır. Demir dışı malzemeler olarak, nikel, kobalt, molibden ve titanyum esaslı malzemeler örnek verilebilir. Borlama işlemi sonucu oluşan borür tabakaları yüksek sertlik ve aşınma direncine sahiptirler. Ayrıca borlama işlemi, korozyon ve oksidasyon direncini arttırmakta ve sürtünme katsayısını düşürmektedir. Borlama yöntemleri: kutu borlama, pasta borlama, sıvı borlama ve gaz borlamadır. Süperalaşımlar, nikel, demir nikel ve kobalt bazlı alaşımlar olup yüksek sıcaklıklarda mekanik özelliklerini ve metalurjik kararlılıklarını muhafaza eden malzeme grubudur. İlk süper alaşımlar östenitik paslanmaz çeliklerin bir modifikasyonu olup günümüzde kullanımda olan birçok malzeme 1950-1970 yılları arasında geliştirilmiştir. 1980?lerde gelişen teknoloji ile bazı elementlerin süperalaşımlara katılabilme olanağının artmasıyla bugün yoğun ilgi duyulan spesifik mekanik özellikler kazanmışlardır. Bu nedenle de yüksek sıcaklık uygulamaları söz konusu olduğunda süperalaşımlar diğer tüm ticari metalurjik malzemelerden daha çok tercih edilmektedirler. Süperalaşımların başlıca uygulama alanlarına uçaklar ve endüstriyel gaz türbinleri (pervane kanatçıkları, yanma odaları, diskler, şaftlar), nükleer güç sistemleri (hareket mekanizmaları için kontrol çubukları, akış valfleri, yaylar), uzay araçları (aerodinamik araç zırhları, roket motor parçaları), petrokimya sanayisi (reaksiyon kapları, borular, pompalar), ısıl işlem ekipmanları ( tepsiler, karıştırıcılar, konveyör bantları) örnek olarak verilebilir. Inconel 718; demir nikel bazlı süperalaşım grubundan olup önemli miktarda nikel, demir ve niyobyum içermektedir. İçerdiği yüksek niyobyum sayesinde çökelti sertleştirmesi ile mukavemetlendirilebilmektedir. Yüksek sıcaklıklarda dahi mekanik özelliklerini (kopma, yorulma, sürünme) korumaktadır. Genel olarak kullanım yerleri; gaz türbinleri, roket motorları, uçak motorları, nükleer reaktörler ve proses ekipmanlarıdır. Demir esaslı malzemelerin termokimyasal yöntemle borlanması üzerine birçok çalışma yapılmış ve son yıllarda bu çalışmalar oldukça hızlanmıştır. Araştırmalar neticesinde elde edilen sonuçlarla birçok gelişmiş ülke, borlama işlemini sanayilerine aktarmıştır. Borlama işlemi endüstriyel olarak daha çok çelikler üzerine uygulanmaktadır ve birçok çelik grubu üzerinde detaylı araştırmalar gerçekleştirilmiştir. Ancak, süperalaşımlar üzerinde yapılan araştırmalar oldukça sınırlıdır ve az sayıda çalışma yapılmıştır. Bu çalışmanın amacı, AMS 5662 ve AMS 5663 ısıl işlemlerine tabi tutulmuş Inconel 718 süperalaşımının, termokimyasal yöntemle borlanması sonucu oluşan fazları tespit etmek ve borlama sonucu oluşan borür tabakasının malzemenin mekanik özelliklerine etkisini incelemektir. Bunun için Inconel 718 süperalaşımına ait numuneler, 800, 900 ve 1000°C sıcaklıklarda 2, 4, 8 ve 12 saat süre ile Ekabor-2 tozu içerisinde kutu borlama yöntemiyle borlanmıştır. Borlama işlemi ardından numunelerin XRD analizi ile faz tayini, SEM ile kesit incelemesi, EPMA analizi ile oluşan tabakaların elementel analizi, sertlik ölçümleri ve aşınma testleri gerçekleştirilmiştir. Yapılan incelemeler sonucu Inconel 718 süperalaşımının borlanması sonucu üç farklı tabakanın meydana geldiği görülmüştür. Bunlardan yüzeye en yakın olanı Ni2Si fazından meydana gelen silisid tabakasıdır. İkinci olarak ise Ni4B3, Fe2B ve FeB fazlarından meydana gelen borür tabakasıdır. Son olarak ise difüzyon tabakası mevcuttur. Artan sıcaklık ve süre ile tabakaların kalınlıkları artmaktadır. AMS 5662 ısıl işlemine tabi tutulmuş numunelerde tabaka kalınlıkları daha fazladır. En yüksek tabaka kalınlığı değeri AMS 5662 Inconel 718 malzemesinin 1000°C'de 12 saat borlanması ile elde edilmiştir. En düşük tabaka kalınlığı ise AMS 5663 Inconel 718' in 800°C'de 2 saat borlanması sonucu elde edilmiştir. Borür tabakasının sertliğinin 1900 HV civarında olduğu saptanmıştır. Yapılan aşınma testleri sonucu yüzeyin sürtünme katsayısının % 50 oranında azaldığı gözlemlenmiştir. Ayrıca malzemenin aşınma direncinde artma saptanmıştır.

If a system works under wear condition, its surface properties are important beside bulk properties. It is necessary to develop surface properties of these materials. There are many coating technologies to develop surface properties of a material. Thermochemical (boriding, nitriding), and thermoreactive diffusion processes (TRD), pack sementation techniques, plasma spray, physical vapour deposition (PVD), chemical vapour deposition (CVD), laser operations etc. are some examples of these technologies. While some of the layers obtained by these techniques form physical bond, some others form strong chemical bond with substrate by diffusion. Boron, in general, used in metallurgy (such as in abrasives, cutting tools, magnets and soldering) for the following purposes; to reduce melting temperature (thus to lower the energy consumed), to increase fluidity (as a fluxing agent), to increase strength (hardenability) of the steel to reduce the corrosion of the refractory material in the furnace. Boron is also used in the production of pure, strong metals to remove the oxygen and nitrogen dissolved in the metal or chemically bound to it. Boron, as a non-metallic solid element, can penetrate and form an alloy with steel under high temperatures. It forms a molecular bond with the metal. Unlike chrome, boron does not add a layer to the original surface. Boron treatment does the opposite. It removes carbon and other impurities from the steel, leaving a pure iron boride layer with boron. Boron can significantly increase the hardenability of steel without loss of ductility. Its effectiveness is most noticeable at lower carbon levels. The addition of boron is usually in very small amounts ranging from 5-30 ppm. Boron, bordering the transition between the metals and non-metals, is regarded as a semiconductor rather than a metallic conductor. Due to its ability to dissolve metal oxide films, as a flux, boron is used in soldering and welding. More specifically, boron trichloride is used in the refining of aluminium, magnesium, zinc, and copper alloys to remove nitrides, carbides, and oxides from molten metal. It has been used successfully as a soldering flux for alloys of aluminium, iron, zinc, tungsten, and monel. Boriding (also known as boronizing) is a thermochemical surface hardening process in which boron atoms are diffused into the surface of work piece to form complex borides with the base metal. There is no mechanical interface between the complex borides and the substrate as this is a true diffusion process. The resulting case layer has a hard, slippery surface capable of performing at higher temperatures than most surface treatments. Practically any ferrous material can be boronized, as well as many Ni, Ti and Co alloys. However, it is important to note, the higher the content of alloy elements, the slower the diffusion rate. There are many kind of boriding techniques. All processes involves heating well-cleaned sample to 800-1000 °C, preferably for 1-12 hours in contact with a boronaceous solid powder or boronizing compound, paste, liquid or gaseos medium. The property of the borided layer depends strongly on the composition and structure of the boride layer and the composition of the base (substrate) material. There are many advantages boriding heat treatmant for materials. First of them, obtained layer has extremly high hardness values. (about 1400-2000 HV) Beside of this, this layer shows excellent resistence to abrasive and adhasive wear with low friction coefficent. In addition, boriding heat treatment increases resistence to corrosion and oxidation. Superalloys is a group of alloys usually based on group VIIA elements and designed for high temperatures where relatively severe mechanical stressing is encountered and where high surface stability is frequently required. In any system where high resistence to under static, fatigue and creep conditions are required, the superalloys are appropriate material group to choice for high temperature applications. The first superalloys are modification of austenitic stainless steels. In 1980s, by developing technology to make alloys for superalloys, some elements have gained excellent mechanical properties, which desired for high temperatures application, to superalloys. Therefore, when the subject is high temperature applications, superalloys are more preferred then other commercial metallurgical materials. However, as high temperature materials are relatively expensive, the superalloys should be employed only after consideration of others that are available. When weight-saving is important, titanium alloys can be preferred instead of superalloys, but their poor oxidation resistence restricts their application to below about 700 °C. For some electricity-generating power plant applications which rely upon superheated steam at about 565oC, high strength creep resistant ferritic steels are preferred on account of their lower cost. The superalloys come into their own particularly in extreme environments, when resistance to oxidation and corrosion is required; for this purpose, they are often used in combination with protective coatings. The superalloys exhibit an outstanding combination of high temperature strenght, excellent creep rupture life, toughness and resistance to oxidation and corrosion. Beyond that, these properties are maintained to elevated temperatures - in some cases to within a few hundred degrees of the melting temperature. For many high temperature applications, other materials are unable to match this combination of properties. Inconel 718; is an iron-nickel based superalloy that contains a significant amount of iron, nickel and niobium. Due to high content of niobium, it can be strenghtened by precipitation mechanism. Inconel 718 is hardened by the precipitation of secondary phases (e.g. gamma prime and gamma double-prime) into the metal matrix. The precipitation of these nickel- (aluminum, titanium, niobium) phases is induced by heat treating in the temperature range of 600 to 800°C. For this metallurgical reaction to properly take place, the aging constituents (aluminum, titanium, niobium) must be in solution (dissolved in the matrix); if they are precipitated as some other phase or are combined in some other form, they will not precipitate correctly and the full strength of the alloy with not be realized. To perform this function, the material must first be solution heat treated. Inconel 718 alloy is used especially aggresive and hot environments. It can be used in gas turbines, rocket engines, aircraft engines, nuclear reactors and process equipments. There are lots of researches on boriding of ferrous materials by thermochemical method and recent years they have accelerated. By results obtained these researches, many developed country have transferred boriding processes to their industries. Industrially, boriding process is applied generally to steels and detailed researches have made on many steel groups. However, researches on boriding of superalloys are limited. The aim of this research is to determine the obtained phases and effect of boride layer to mechanical properties of thermochemical borided AMS 5662 and AMS 5663 heat treatment applied Inconel 718 superalloy. For this, samples of Inconel 718 superalloy were borided in 800, 900 and 1000°C for 2, 4, 8 and 12 hours in Ekabor-2 powder by pack boriding. After boriding process, examinition of cross section by SEM (scanning electron microscobe), phase determination by XRD (X-ray diffractometer), elementel analyse of obtained layers by EPMA (electron probe microanalyser), hardness measurements and wear tests were applied borided samples. According to results of these investigations, it has determined that obtained layer, by boriding of Inconel 718 superalloy, has three distinct layers. The first layer of these layers, which most closed to surface is silicid layer, contains Ni2Si phase. Second layer is boride layer consists of Ni4B3 and FeB. The last layer is diffusion layer. Thickness of all layers increases by increasing time and temperature. AMS 5662 heat treated Inconel 718 superalloy has higher thickness then AMS 5663 heat treated. The highest thickness is attained in borided AMS 5662 Inconel 718 superalloy in 1000 C for 12 hours and the lowest thickness is attained in borided AMS 5663 Inconel 718 superalloy in 800°C for 2 hours. Hardness values are up to 1600 HV in boride layer. Also wear resistence develops by boriding heat treatment.
Thermochemical boriding of Inconel 718 superalloy
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Keywords: Aşınma; Borlama; Süper alaşımlar; Wear; Boriding; Superalloys